Tidal Constraints on the Martian Interior. Issue 11 (27th October 2022) - Pou, L.; Nimmo, F.; Rivoldini, A.; Khan, A.; Bagheri, A.; Gray, T.; Samuel, H.; Lognonné, P.; Plesa, A.‐C.; Gudkova, T.; Giardini, D.
Abstract: We compare several recent Martian interior models and evaluate how these are impacted by the tidal constraints provided by the Love number k 2 and the secular acceleration in longitude s of its main moon, Phobos. The expression of the latter is developed up to harmonic degree 5 to match the accuracy of the current observations. We match a number of current interior structure models to the recent measurements of the tidal parameters and derive estimations of the possible core radius, temperature profile, and attenuation in the Martian interior. Our estimation of the core radius is 1, 820 ± 80 km, consistent with recent seismic measurements. The attenuation profiles in the Martian interior at the main tidal period of Phobos are similar between the considered models, giving a range for the degree‐2 bulk tidal attenuation Q 2 = 93.0 ± 8.40 but diverge at seismic frequencies. At seismic frequencies, model shear attenuation Q μ ranges between 100 and 4, 000 in the lower mantle, so that a measurement of seismic shear attenuation could be used as an effective means for distinguishing between the models considered. Other constraints such as elastic lithosphere thickness and Chandler Wobble period favor a thicker elastic lithosphere and models with a frequency dependence α of the shear attenuation between 0.15 and 0.4. Improved constraints on the Martian interior should be possible with additional seismic and radio observations from the InSight mission. Plain Language Summary: The largest moon of Mars, Phobos, raises tides on the red planet causing its surface to be deformed. The size of this tidal bulge depends on the elastic properties of Mars, while viscosity and anelasticity inside the planet cause the tidal bulge to be misaligned with the position of Phobos on its orbit. This misalignment between Phobos and the tidal bulge of Mars creates an acceleration in longitude for the moon, which can be measured and used with the size of the tidal bulge to constraint the interior of Mars. Both the size and orientation of the tidal bulge can be used as tidal constraints to probe the size of the core of Mars, the temperature profile in its interior, and how strong the viscous dissipation is in its mantle. Our current estimates give a wide range of possible attenuation in the Martian mantle, favoring larger core sizes with larger elastic thickness of the lithosphere, the rigid outermost layer of a solid planet. Knowledge of the Martian interior could be further improved with future seismic and radio measurements from the InSight mission. Key Points: We develop a formulation to calculate the secular acceleration of Phobos due to tidal dissipation in Mars Using the Love number k 2 and the secular acceleration s, we obtain for Mars a core size of 1, 820 ± 80 km and a bulk Q of 93.0 ± 8.40 We discuss several means to distinguish between Mars models using seismological, rotational, and lithospheric observations